2005
DOI: 10.1111/j.1464-5491.2005.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Attentional functioning is impaired during acute hypoglycaemia in people with Type 1 diabetes

Abstract: In people with Type 1 diabetes, hypoglycaemia causes a significant deterioration in attentional abilities, while non-verbal reasoning is preserved. It is likely therefore that many complex cognitive tasks which involve attention will be impaired during moderate hypoglycaemia during everyday life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
(42 reference statements)
0
22
0
Order By: Relevance
“…Luchsinger et al (2007) have argued that the amnestic type is more typical for diabetes-associated mild cognitive dysfunction because non-amnestic cognitive impairment may be due to other factors, including vascular risk factors. In our study, visual and verbal working memory excluding short-term memory was impaired, indicating that tasks with higher cognitivethat is, executive-demands may be more sensitive for detecting cognitive dysfunction in diabetes (see also Heller &Macdonald, 1996, andMcAulay et al, 2006). Bruehl et al (2007) found elevated plasma cortisol levels and declarative memory deficits in middle-aged individuals with DM2 indicating hypothalamic-pituitaryadrenocortical (HPA) hyperactivity.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Luchsinger et al (2007) have argued that the amnestic type is more typical for diabetes-associated mild cognitive dysfunction because non-amnestic cognitive impairment may be due to other factors, including vascular risk factors. In our study, visual and verbal working memory excluding short-term memory was impaired, indicating that tasks with higher cognitivethat is, executive-demands may be more sensitive for detecting cognitive dysfunction in diabetes (see also Heller &Macdonald, 1996, andMcAulay et al, 2006). Bruehl et al (2007) found elevated plasma cortisol levels and declarative memory deficits in middle-aged individuals with DM2 indicating hypothalamic-pituitaryadrenocortical (HPA) hyperactivity.…”
Section: Discussionmentioning
confidence: 67%
“…Some researchers discovered specific cognitive deficits, including impaired information processing speed and memory (e.g., Gold et al, 2007;McAulay, Deary, Sommerfield, & Frier, 2006;Warren, Zammitt, Deary, & Frier, 2007), while others reported reduced performance particularly in tasks that require higher mental efficiency (e.g., Brands, Bissels, et al, 2007;Watari et al, 2006; for a review, see also Heller & Macdonald, 1996). The presence and severity of cognitive impairments appear to be associated with the duration of illness and glycemic control.…”
mentioning
confidence: 95%
“…The video required sustained attention for around 10 min, and attention has been shown to be impaired during hypoglycaemia [33,34]. Deterioration of visual information processing may have reduced the subjects' ability to glean information from the video [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the executive function and memory function were both significantly affected by severe hypoglycaemia [53,55,58,[72][73][74][75][76][77][78][79][80].…”
Section: Hypoglycaemiamentioning
confidence: 99%